Spectroscopic and Thermal Study of the Cyanide-Bridged Heteronuclear Compounds [Cd(NH3)(?-3-Aminomethylpyridine)M(?-CN)4]N [M: Pd(II) or Pt(II)] - Karaagac, Dursun; Kurkcuoglu, Gunes Suheyla (Springer, 2024)
New cyanide-bridged heteronuclear compounds, [Cd(NH3)(mu-ampy)M(mu-CN)(4)](n) [ampy = 3-aminomethylpyridine, M: Pd(II) or Pt(II) (hereafter abbreviated as Cd-M-ampy)] have been prepared in powder form and investigated by utilizing elemental analysis, vibrational (FT-IR and Raman) spectroscopy, and thermal analysis. In our previous work, we synthesized the [Cd(NH3)(mu-ampy)Ni(mu-CN)(4)](n) compound and determined its crystal structure. The results of thermal analysis and vibrational spectroscopic show that the structural characteristics of Cd-Ni-ampy and Cd-M-ampy [M: Pd(II) or Pt(II)] compounds are analogous to each other. In these compounds, while the sphere of the center of the M(II) ion has a square pyramidal geometry, the coordination sphere of the Cd(II) ion is identified to have a distorted octahedral geometry. While one amine, one ampy, and four cyanide ligands coordinate to the Cd(II) ion, a three-dimensional coordination polymer forms by the coordination of these ligands to the Cd(II) and M(II) ions. Thermal degradation of the compounds occurs in two steps: degradation of ampy and amine ligands and release of the cyanide groups.
Keywords: tetracyanometallate(II) compounds; 3-aminomethylpyridine compounds; heteronuclear compounds; cyanide compounds